Bog - Krossing, Karen (Fitzhenry & Whiteside, 2014)
When his father is mercilessly turned to stone by the Troll Hunter's followers, a cave troll named Bog sets out to find the murderers and avenge his father. But with no leads and little knowledge of the human world, Bog knows his journey won't be easy. Along the way he meets a huge forest troll named Small and a young human girl named Hannie. Together, they venture deeper into human territory, where they learn of the legendary Nose Stone-- a rock rumoured to bring a stone troll back to life. Hope fills Bog's heart, but when he discovers the Troll Hunter is also going after the Nose Stone to destroy it, his quest becomes a race of cunning, trickery, and wits. --